Virtualization as the Evolution of Operating Systems - Tudor Zaharia (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2010)
Although virtualization has been around for more than 50 years, the subject is hotter than ever. Initiated to simulate multiple machines using hardware and software techniques, virtualization today brings server consolidation, security and isolation for multiple operating systems running on the same hardware. This article’s main objective is to show that virtual machines are just another step in the evolution of operating systems. I will argue that in fact a virtual machine monitor is a resource manager just like an operating system is. Important points like CPU and memory management are going to be addressed. Although not exhaustive, this paper will discuss the most important attributes of virtual machine monitors as operating systems and my view on how the field should evolve in this new light.